The motivational level of performance swimmers and its impact on the risk of sports dropout - Brat, V.; Bota, A.; Mitrache, G.; Teodorescu, S. (Sports, 2025)
Background: Motivation is a crucial factor in maintaining athletic performance and preventing dropout among competitive athletes. This process is influenced by both physical and psychosocial factors, which interact and shape decision—making regarding continued participation or withdrawal from sports.